Correlates of loneliness among university students - Tuncay Tarik; Özdemir Ugur (BMC, 2008)
Abstract Background The purpose of this study was to investigate level of loneliness, essential needs during university education, and relationships between loneliness, essential needs, and characteristics of university students. A sample comprising 721 students participated in the study. The mean age was 21.58 (SD = 1.73) with a range from 18 to 25. The majority of the students were female (70.6%) and were living in students' dormitory (67.5%) with low (87.8%) income, away from their parents. Methods The UCLA-R loneliness scale and sociodemographic questionnaire which includes an open-ended question on essential needs during university education were administered. Pearson-Product-Moment correlations were used to explore the relationships between participants' loneliness, needs, and characteristics. Results It was found that 60.2% of the participants experienced loneliness. Economical support (81.6%), social interaction (46.9%) and psychosocial support (35%) were the essential needs during university education reported by the participants. The study findings indicate that there were significant relationships between the needs of economical support, social interaction, and loneliness level of university students. Results also show that there were significant relationships among romantic relationship, parents' status and loneliness. Participants' loneliness levels were relatively higher who had not any romantic relationship and were not from married families. Conclusion The findings of this study provided essential information, about Turkish university students, concerning: level of loneliness and relationships that exist among loneliness, needs and sociodemographic characteristics. The findings also suggest implications for psychosocial practice. Because of the mean of loneliness were found to be high (45.49 ± 10.07), for this study, professionals need to pay attention to Turkish university students' psychosocial state, and need to empower them in establishing social relations.